Types of Speech Styles Used at G20 Summit Forum: A Sociolinguistics Perspective - I Gede Tangkas Yoganandita; Ni Nyoman Tri Sukarsih; Ni Luh Desy Suari Dewi (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2023)
Speech style is the form of language used by the speaker influenced by social factors. Ethnography of communication is an approach a perspective and method to and is a study culturally distinctive means and meanings of communication. This study aims to identify types of speech style using theory of speech style proposed by Joos (1972). The qualitative method was used in this study where the data was taken from the utterance of speech style and the ethnography of the communication found in Mr. Joko Widodo’s speech at G20 Summit Bali Indonesia on YouTube and Cabinet Secretariat Indonesia website using observation, documentation, and note-taking technique. The analysis showed that the utterance of Mr. Joko Widodo’s speech used five types of speech style, there were: Frozen style 5, formal style 15, consultative style 1, casual style 1, and intimate style 1.